2006
DOI: 10.1002/aic.10961
|View full text |Cite
|
Sign up to set email alerts
|

Particle wetting distribution in trickle‐bed reactors

Abstract: in Wiley InterScience (www.interscience.wiley.com).A novel technique is used to obtain the distribution of particle wetting in trickle-bed reactors for different flow and prewetting conditions. Two prewetting methods were investigated: (1) Levec prewetting, in which the packed catalyst bed is completely flooded and then left to drain before steady state trickle-flow is commenced; (2) Kan prewetting, in which the bed is prewetted by pulsing with the liquid before flow, after which the liquid flow is gradually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 22 publications
(46 reference statements)
2
35
0
2
Order By: Relevance
“…Khadilkar et al 18 also showed the down flow mode to be superior to the upflow mode for gas-limited conditions, leading one to expect the Levec mode to outperform the Kan-Liquid mode in this case. For severely gas-limited reactions, Van Houwelingen et al 10 also expected the Levec mode to outperform the Kan-Liquid mode. This is because the lower wetting efficiency (more gas-solid area) in the Levec mode allows greater access for the gas phase to the particle interior through the gas-solid surface area (although it is also likely to be more prone to liquid diffusional limitations due to the presence of particles with very low wetting efficiencies).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Khadilkar et al 18 also showed the down flow mode to be superior to the upflow mode for gas-limited conditions, leading one to expect the Levec mode to outperform the Kan-Liquid mode in this case. For severely gas-limited reactions, Van Houwelingen et al 10 also expected the Levec mode to outperform the Kan-Liquid mode. This is because the lower wetting efficiency (more gas-solid area) in the Levec mode allows greater access for the gas phase to the particle interior through the gas-solid surface area (although it is also likely to be more prone to liquid diffusional limitations due to the presence of particles with very low wetting efficiencies).…”
mentioning
confidence: 94%
“…While the discussion has thus far used pressure drop as an example, it is important to note that similar loops exist for holdup, the gas-liquid volumetric mass transfer coefficient 8 and for wetting efficiency. 10 The terms hydrodynamic multiplicity and hysteresis therefore refer to variation in all the hydrodynamic parameters as a result of flow rate changes or prewetting methods. For liquid flow rate variation induced hysteresis in prewetted beds, the two limiting modes are those shown schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…out of three conventional trays i.e. sieve tray, bubble cap tray and valve tray [11][12][13][14]. Although distillation is generally recognized as one of the best developed chemical processing technologies there are still many technical barriers, mainly related to equipment performance, that could, when overcome, secure the position of the distillation and even make it more attractive for use in future.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of this first treatment, an average value of the wetting efficiency on the section can be calculated as the surface ratio of the red zones to the sum of the white and red zones. (1) Column, (3 and 39) liquid storage tanks (pure/colored), (8) hollowed headspace of the distributor, (9) capillaries, (10) gas inlet, (11) gas distributor, (12) piston to move the inner column, and (13) hinged jib supporting the camera.…”
Section: Two-dimensional Monolayer Of Pelletsmentioning
confidence: 99%
“…Very recently, van Houwelingen et al 12 used a similar technique to derive wetting efficiencies for different modes of prewetting.…”
Section: Introductionmentioning
confidence: 99%